Sistem Pencatatan Kehadiran Berbasis Java Card - Lidya Octarina (Bina Nusantara University, 2010)
The purposes of this research are to prevent jockey in exams, reduce the occurrence of error in attendance record at practicum or exams, and reduce error in filling students' attendance status to the attendance system. Three main parts of software development method are used; analysis, design, and literature method. Current system survey, analysis of the survey findings, identify the information, and identifying system requirements are implemented in analysis method. The design method that is used in this research is Unified Modeling Language (UML). The using of attendance recording system that uses Java Card-based application makes students identity card has a new function as the tool to make attendance. Conclusion of the research has shown that it can prevent identity fraud, minimize the time wasted in attendance system, reduce the printing paper, and reduce tagging errors eligibility status exam of students.